Penentuan Status Mutu dan Beban Pencemaran Air Kali Dendeng Kota Kupang - MARIA MAGDALENA KOLO (Fakultas Pertanian, Universitas Timor, 2019)
The research of determination the status of water quality and pollution loads in Dendeng river using pollution index has been conducted. The aims of this research are to determine the water quality status and to determine the pollution loads of Dendeng river. The parameters measured are: ph, DO, BOD, COD, Suspended Solid Total, N-NO3 and N-NH3 in order to determine the water quality status, while parameters BOD, COD and TSS were used to determine the pollution loads. The result of this research showed that the water quality status from the five station which was observed by the research was classified as light of pollution index value for each station was 3.178 for station I, 3.788 for station II, 3.064 for station III, 4.124 for station IV and station V was 3.806. The total average of pollution loads based on the parameter of BOD, COD and TSS of the five station were 190741.87, 3085891.79 and 266967.03 tons/year, respectively.